On the Pipe Localization Based on the Unwrapped Phase of Ground Surface Vibration Between a Roving Pair of Sensors - Iwanaga, Mauricio Kiotsune [UNESP]; Brennan, Michael John [UNESP]; Scussel, Oscar; de Almeida, Fabrício César Lobato [UNESP]; Karimi, Mahmoud (Springer Nature, 2023)
Buried pipes are used worldwide to transport water. Although they are convenient, a large amount of water is wasted during the transportation. To minimize such a problem, water companies apply different technologies to locate leaks in their pipe networks, where the buried pipe is usually located first. Electromagnetic techniques can be used to locate buried pipes, but their performance is limited by the moisture content of the surrounding soil. Active vibro-acoustic techniques have also been investigated to locate buried pipes, in which vibro-acoustic energy is introduced into the soil by an excitation source. Although they are promising, their practical application can be expensive and complex due to the setup of an excitation mechanism. The aim of this paper is to present a passive vibro-acoustic localization technique for buried water pipes, in which a leak is the source of excitation. The localization technique is based on the calculation of an approximate slope for the unwrapped phase between a pair of sensors placed on the ground surface. The performance of the two-sensor technique is tested with two datasets, one extracted from a numerical model of the buried pipe system and the other extracted from an experiment carried out on a test rig. The results highlight the potential of the two-sensor technique in locating buried water pipes.
Keywords: Buried pipe localization; Ground surface vibration; Pair of sensors; Unwrapped phase